109 The walton headache pathway – design and outcome. Issue 12 (14th November 2019) - Fletcher, Nicholas; Krishnan, Anita; Silver, Nicholas; Riley, Julie; Wilson, Martin; Nicolson, Andrew
Abstract : Headache is a major component of increasing demand in neurology secondary care - mainly migraine and other primary headache disorders. A headache pathway was developed at the Walton Centre (WCFT), with local GPs, to facilitate and support the diagnosis and management of primary headache disorders (migraine, medication overuse headache and tension headache) in primary care. The pathway was intended to reduce avoidable referrals of patients with straightforward primary headaches to secondary care and improve identification and referral of those with refractory primary headaches, any other (potentially more serious) form of headache or those in whom use of the pathway did not lead to a primary care diagnosis. This was adopted by seven local CCGs after extensive engagement with commissioners and GP educational sessions. The outcome of the pathway in 2016–2018 was a 24% reduction in headache referrals; new patients seen in outpatients with headache reduced by 22%; attendances with migraine reduced by 20% and the number of headache patients discharged after one attendance (a surrogate marker for patients who potentially could have been managed in primary care) reduced by 42%. These results indicate that more patients with migraine and other primary headache disorders were offered more faster treatment in primary care rather than after hospital referral. With clinical engagement, it is possible to share a simple pathway with GPs to reduce headache referral demand in secondary care.